2020
DOI: 10.1111/fcp.12530
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of phosphodiesterase 3, 4, and 5 inhibitors in amelioration of high‐fat diet‐induced nonalcoholic fatty liver in rats

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a highly prevalent disease linked to insulin resistance, oxidative stress, and cytokine imbalance. Phosphodiesterase (PDE) inhibitors have shown remarkable antioxidant and anti-inflammatory potential in different disease sets including liver diseases. This study aimed to compare the ameliorative effect of different PDE inhibitors on a high-fat diet (HFD)-induced NAFLD. Male Wistar rats were fed a HFD for 16 weeks to induce NAFLD, and then, oral treatments of a vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Mechanistically, miR-137-3p is directly bound to the 3′-UTR of PDE4D, a cAMP-specific phosphodiesterase, and subsequently increased hepatic cAMP level and PKA activity, thereby activating the downstream AMPK α pathway. Consistently, other findings also proved that the treatment with PDE inhibitors could protect against HFD-induced NAFLD [ 55 , 56 ]. Beyond AMPK α , many other downstream targets of miR-137-3p have been proposed.…”
Section: Discussionsupporting
confidence: 75%
“…Mechanistically, miR-137-3p is directly bound to the 3′-UTR of PDE4D, a cAMP-specific phosphodiesterase, and subsequently increased hepatic cAMP level and PKA activity, thereby activating the downstream AMPK α pathway. Consistently, other findings also proved that the treatment with PDE inhibitors could protect against HFD-induced NAFLD [ 55 , 56 ]. Beyond AMPK α , many other downstream targets of miR-137-3p have been proposed.…”
Section: Discussionsupporting
confidence: 75%
“…Blood samples were collected by cardiac puncture and centrifuged for 10 min to obtain serum. After that, rats were sacrificed by decapitation and the livers were collected rinsed extensively in cold PBS and preserved for histopathological examination, oxidative stress, and inflammatory markers [13]. TC, TGs, HDL, LDL, VLDL, AST, ALP, ALT, and AI bilirubin were measured as described previously [14] while CRI calculated using formula [15].…”
Section: Hfd-induced Hyperlipidemiamentioning
confidence: 99%
“…This result is in accordance with earlier studies that have reported the anti-inflammatory properties of Cilo in different experimental models of testicular injury [ 11 , 21 ]. Furthermore, the protective effect of Cilo against diclofenac-induced renal toxicity [ 37 ], high-fat-diet-induced nonalcoholic fatty liver [ 38 ], and cyclophosphamide-induced cardiac damage [ 39 ] has been partially attributed to its ability to diminish the level of inflammatory markers. Milrinone also dramatically decreases TNF-α levels, which contributes to its ameliorative effect against ischemia-reperfusion testicular injury [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the potent anti-inflammatory properties of PTX have been documented in various illnesses [ 44 ]. PTX decreased TNF-α and NF-κB in cerebral ischemia reperfusion [ 45 ], high-fat-diet-induced nonalcoholic fatty liver [ 38 ], and diclofenac-induced acute renal injury [ 37 ] models. Importantly, the decline in NF-κB and TNF-α expression was more pronounced in CIS rats treated with 20 mg of Cilo compared to either the TDF or the PTX group.…”
Section: Discussionmentioning
confidence: 99%